2012
DOI: 10.1159/000341371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cetuximab in Combination with FOLFIRI in a Patient with KRAS Wild-Type Metastatic Anal Cancer

Abstract: Anal canal cancer is a rare tumor without clear treatment evidence in the metastatic setting. In terms of the bad prognosis of patients with metastatic anal cancer, further therapeutic options are urgently needed. In this paper we present the case of a 64-year-old man suffering from undifferentiated squamous cell carcinoma with liver metastases. After progression on cisplatin and fluorouracil, tumor tissue was analyzed with respect to anti-EGFR therapy with cetuximab. There was no KRAS mutation and the EGFR ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Severe skin rash (grade 3/4) has been reported in 5-20% of patients who receive cetuximabbased treatment [24] . In contrast, no severe skin toxicities were observed in this study (only grade 1/2 rash of 39%), which is consistent with previous case and case series reports of cetuximab monotherapy or cetuximab combined with chemotherapy in metastatic SCCA [6,[13][14][15] . One possible explanation for the lack of severe skin toxicities is the limited number of patients in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Severe skin rash (grade 3/4) has been reported in 5-20% of patients who receive cetuximabbased treatment [24] . In contrast, no severe skin toxicities were observed in this study (only grade 1/2 rash of 39%), which is consistent with previous case and case series reports of cetuximab monotherapy or cetuximab combined with chemotherapy in metastatic SCCA [6,[13][14][15] . One possible explanation for the lack of severe skin toxicities is the limited number of patients in our study.…”
Section: Discussionsupporting
confidence: 92%
“…A number of previous studies have demonstrated universal expression of EGFR in anal squamous cell carcinomas [7,8,11] , and several case studies showed clinical efficacy of EGFR inhibitors in patients with metastatic anal cancer [6,[12][13][14][15] . However, these successes with targeting EGFR remain anecdotal due to the limited number of patients in each case study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, yet another study demonstrated high toxicity of cetuximab therapy [42]. At present, evaluation of any benefit of cetuximab or panitumumab in the therapy of metastatic anal cancer is available mostly in the form of case reports [39,[43][44][45]. As mentioned above, worse tolerance of the therapy is a problem in the combination of antiEGFR therapy and chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab is a monoclonal antibody against the EGFR and, in combination with systemic chemotherapy, has been shown to reduce size of liver metastases in advanced disease [104,105]. While the high rate of EGFR expression and low KRAS mutation rate makes the use of EGFR inhibitors attractive, there is little published work in this area.…”
Section: Future Strategiesmentioning
confidence: 99%